The application of conceptual modelling to assess the impacts of future climate change on the hydrological response of the Harvey River catchment - Al-Safi, H.; Sarukkalige, Priyantha Ranjan (2018)
This paper presents an assessment of the impacts of future climate changes on the hydrological characteristics of Harvey River catchment in Western Australia. A conceptual lumped-parameter rainfall-runoff model (HBV model) is used to simulate the catchment hydrological behaviour. Daily observations of rainfall, temperature and discharge and monthly mean potential evapotranspiration from the hydro-meteorological stations within the catchment were used to calibrate and validate the HBV model. The calibrated model was then forced by the downscaled future rainfall and temperature to simulate the daily discharge at the catchment outlet for the mid (2046-2065) and late (2080-2099) of the 21st century. Future climate signals were extracted from a multi-model ensemble of eight Global Climate Models (GCMs) from the Coupled Model Intercomparison Project Phase 5 (CMIP5) under three Representative Concentration Pathways (RCPs) (RCP2.6, RCP4.5 and RCP8.5). A control run, with the baseline climatic period (1971-2010), was used to represent the current climate status. Results show a noticeable reduction in the mean annual streamflow during the mid-century particularly for the RCP4.5 relative to the current streamflow. By the end of the century, all scenarios revealed a relatively high decline in the mean annual streamflow especially the RCP4.5. The decline in future streamflow ranged between 17-27% during the mid-century and 23-52% by the end of the century.